2017
DOI: 10.1097/md.0000000000008587
|View full text |Cite
|
Sign up to set email alerts
|

Indications and outcomes of pediatric keratoplasty in a tertiary eye care center

Abstract: To evaluate indications and outcomes of pediatric keratoplasty in a tertiary eye center, and identify factors that affect visual outcomes.We performed a retrospective review of penetrating keratoplasty in children aged 0 to 18 years between 1995 and 2011 in the Asociación para Evitar la Ceguera en México IAP, Hospital “Dr. Luis Sánchez Bulnes”.A total of 574 penetrating keratoplasties were performed during the study interval. Median follow-up was 5.0 years. Main indications included keratoconus (55.58%), posth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
2
17
0
1
Order By: Relevance
“…A higher risk for rejection of penetrating grafts has been well recognized in the pediatric population. 44 To our knowledge this is the first report that among recipients older than 50 years old, graft rejection following DSAEK is more likely in younger recipients, as has been noted with high rejection risk PKP cases. 27 This may be the result of the immune system becoming less active with increasing age, 45…”
Section: Discussionmentioning
confidence: 55%
“…A higher risk for rejection of penetrating grafts has been well recognized in the pediatric population. 44 To our knowledge this is the first report that among recipients older than 50 years old, graft rejection following DSAEK is more likely in younger recipients, as has been noted with high rejection risk PKP cases. 27 This may be the result of the immune system becoming less active with increasing age, 45…”
Section: Discussionmentioning
confidence: 55%
“…36 The higher prevalence of Peters' anomaly with associated cataract and glaucoma could explain some of the relationship between pediatric PKs and graft failure. Another possible explanation for poorer graft outcomes in children is the more robust immune response in younger individuals, 37 which could lead to a higher risk of graft rejection compared to adults. We performed an additional analysis of graft survival comparing patients ≤10 years old and > 10 years old at the time of PK, which revealed that the younger age group had a 1.81 greater probability of graft failure as compared to the older age group ( P = .008).…”
Section: Discussionmentioning
confidence: 99%
“…[ 89 ] Gulias-Cañizo et al found in their recent retrospective review of a large series of 574 pediatric keratoplasties, KC showed the best graft survival at 60-months follow-up of 85%, as compared to other indications. [ 93 ] The Australian Registry Study on corneal transplantation in KC in all age groups observed significantly better outcomes with the first PK for KC to have a significantly better survival of 89% at 10 years in comparison to 49% at 20 years. [ 92 ]…”
Section: Management Protocolmentioning
confidence: 99%
“…The addition of topical cyclosporine can help reduce the long-term corticosteroid use required to alleviate graft rejection in children. [ 97 ] The Urret–Zavalia syndrome can occur, especially after DALK, with the prolonged anterior chamber filling with a tight air bubble, as with cases of long drawn of anterior lamellar dissection as in BB-DALK[ 93 ] or after tight pneumopexy for DM perforation. [ 82 ] Though the exact pathogenesis is not clear, pressure-induced ischemic necrosis is postulated to cause dilated and fixed pupil, iris atrophy, and even cataract.…”
Section: Management Protocolmentioning
confidence: 99%